2022
DOI: 10.1002/jgm.3451
|View full text |Cite
|
Sign up to set email alerts
|

The CHST11 gene is linked to lung cancer and pulmonary fibrosis

Abstract: Background The abnormal modification of chondroitin sulfate is one of the leading causes of disease, including cancer progression. During chondroitin sulfate biosynthesis, the CHST11 enzyme plays a vital role in its modification, but its role in cancer is not fully understood. Therefore, understanding the relationship between CHST11 and pulmonary‐related diseases through clinically relevant information may be useful for diagnosis or treatment. Methods A variety of pulmonary fibrosis clinical gene expression om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…According to previous studies, CHST11 is abnormally expressed in various malignant tumors, and it is closely associated with the clinicopathological features of cancer and the prognosis of cancer patients. Li et al 28 found that the CHST11 expression level was significantly elevated in lung cancer tissues and correlated with a poor patient prognosis. Relevant studies have indicated that CHST11 may promote the progression of endometrial cancer by activating pathways such as the Wnt signaling pathway and promoting epithelial-mesenchymal transition 29 .…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, CHST11 is abnormally expressed in various malignant tumors, and it is closely associated with the clinicopathological features of cancer and the prognosis of cancer patients. Li et al 28 found that the CHST11 expression level was significantly elevated in lung cancer tissues and correlated with a poor patient prognosis. Relevant studies have indicated that CHST11 may promote the progression of endometrial cancer by activating pathways such as the Wnt signaling pathway and promoting epithelial-mesenchymal transition 29 .…”
Section: Discussionmentioning
confidence: 99%